2022
DOI: 10.3390/pathogens11121454
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Pathogen Causing Leaf Spot in Zinnia elegans and Its Sensitivity to Five Fungicides

Abstract: Zinnia elegans Jacq. is an important, globally cultivated ornamental plant. In August 2021, a leaf spot disease was observed in zinnia in Shibing County, Guizhou, China, with an incidence of approximately 60%. Pathogens were isolated and purified from the infected leaves by tissue isolation, and pathogen strain BRJ2 was confirmed as the pathogen causing the leaf spot. Based on morphology and ITS, TEF-1α, and TUB2 sequence analyses, the pathogen was identified as Nigrospora musae (McLennan and Hoëtte). The myce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…In the present study, the two species were distinct from other Pestalotioid species found in Chinese yew ( Chen et al 2002 ; Ding et al 2009 ; Liu et al 2010 ; Ismail et al 2013 ; Li 2017 ; Subban et al 2019 ; Qi et al 2022 ; Sun et al 2023 ). Morphologically, the conidia of P. taxicola and P. multicolor are smaller (16.5–21 × 4–6 μm and 14.5–20 × 3.5–5.5 μm, respectively).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…In the present study, the two species were distinct from other Pestalotioid species found in Chinese yew ( Chen et al 2002 ; Ding et al 2009 ; Liu et al 2010 ; Ismail et al 2013 ; Li 2017 ; Subban et al 2019 ; Qi et al 2022 ; Sun et al 2023 ). Morphologically, the conidia of P. taxicola and P. multicolor are smaller (16.5–21 × 4–6 μm and 14.5–20 × 3.5–5.5 μm, respectively).…”
Section: Discussionsupporting
confidence: 45%
“…The expansion of Chinese yew cultivation in recent years has led to the emergence of various diseases that pose a significant threat to the Chinese yew industry ( Zhang et al 2018 ). Many fungal pathogens have been reported to cause Chinese yew diseases during their growth, such as needle spot caused by Neopestalotiopsis clavispora and Pestalotiopsis affinis ( Chen et al 2002 ; Wang et al 2019 ), needle blight caused by Pestalotiopsis microspora ( Li 2017 ), anthracnose disease caused by Colletotrichum gloeosporioides ( Fan et al 2006 ) and wilt disease caused by Phoma sp., while Fusarium oxysporum is responsible for root rot ( Qian et al 2015 ). Needle diseases caused by Pestalotioid fungal species (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is mainly produced in China, far east Russia, the Korean Peninsula, and Japan, where its production vitalizes rural areas and alleviates poverty; it is widely produced in Guizhou Province, China, where there is over 20,000 hm 2 of planting area [8]. Moreover, LSD is a serious fungal disease that affects P. heterophylla, frequently leading to economic losses of more than 50% [9][10][11][12]. In the early stage of LSD, brown round or irregular spots appear on the leaves; these then gradually expand, and the center of the spots becomes grayish white or light yellow-brown before dead spots are formed in the later stage.…”
Section: Introductionmentioning
confidence: 99%